THE IMPACT OF DIAPHRAGM WALL PENETRATION DEPTH ON EXCAVATION STABILITY FOR THE MRT STATION PROJECT - Aji Abdilla, Muhammad
The Sawah Besar MRT Station project is a a deep excavation project located in central Jakarta. The construction of this station is being carried out along Jalan Gadjah Mada, an area surrounded by tall buildings and the Ciliwung River. The project’s limited workspace present challenges, requiring the implementation of a top-dwon construction approach with reinforced concrete slab struts.This final report covers various aspect, including the interpretation of soil data from site investigation, determination of penetration depth, stability checks. Lateral deflection limit checks, reinforcement of the diaphragm wall, and dewatering design. Additionally, the report analyzes the impact of diaphragm wall penetration depth on safety factors, seepage quantities, and deflection. Modeling using PLAXIS 2D software explores three variations of penetration depth: 18, 22, and 26 meters. Based on the results from global stability checks, base excavation stability, and lateral deflection limits, the 18-meter penetration depth is selected as the recommended design for the Sawah Besar MRT Station project. The analysis of the diaphragm wall penetration depth shows that the safety factor for global stability and base excavation increases with greater penetration depth. Additionally, the analysis reveals that the amount of seepage entering the excavation area decreases as the diaphragm, wall penetration depth increases.